2015
DOI: 10.1089/jpm.2014.0386
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences versus Family Physicians' Perceptions Regarding the Place of End-of-Life Care and Death: A Nationwide Study in Taiwan

Abstract: Background: Enabling people to die in their preferred place is important for providing high-quality end-of-life care. Objective: The study objective was to explore patients' preferences regarding the place of end-of-life care and death and to compare these preferences with the perceptions of their family physicians. Methods: This cross-sectional study used stratified random sampling, surveying 400 registered patients and 200 of their family physicians nationwide, with a five-part, structured, self-report quest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 29 publications
0
34
0
5
Order By: Relevance
“…The place of death is a major theme among patients in palliative care delivery research. Most patients at the end of life prefer dying at home [14]. The result demonstrated the greatest needs of a majority of patients that they require better understanding about their diseases, prognosis and medical treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The place of death is a major theme among patients in palliative care delivery research. Most patients at the end of life prefer dying at home [14]. The result demonstrated the greatest needs of a majority of patients that they require better understanding about their diseases, prognosis and medical treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The ultimate goal is to provide patients and families with the best QOL during the trajectory of diseases [11]. The data from previous studies showed that many terminally ill patients would prefer to stay and die in their own homes, but unfortunately some of patients may not be able to do so [11][12][13][14]. Evidence has presented many benefits of home care for palliative care patients.…”
Section: Introductionmentioning
confidence: 99%
“…The data from previous studies showed that many terminally ill patients would prefer to stay and die in their own homes, but unfortunately, some patients may not be able to do so. [1][2][3][4][5][6] Even though there are many factors associated with successful home deaths (ie, the patient's or family's preference, the patient's performance status during the last days, the patient's awareness of the disease status and prognosis), receiving palliative home visits from the multidisciplinary care teams is one of the key factors that enable patients to die at home. [7][8][9][10][11] Previous evidence has supported many benefits of home care for palliative care patients.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, in Taiwan, the rates of home death preferences were almost as high as those observed in European countries, although the underlying rationale could not be more different. A survey carried out with patients registered with family physician clinics found that home was the preferred location of death by 67% of the respondents (Shih et al, 2015). Despite strong reservations about burdening the family to fulfill their wish to die at home (Shih et al, 2015), the majority of cancer patients surveyed in a separate study also preferred home as the place of death (C.…”
Section: Preferences In Asian Countriesmentioning
confidence: 99%
“…If death were to occur outside of the home, for instance, in the hospital, it is believed that the spirit might become a wandering and forsaken ghost (S.-Y. Cheng et al, 2015;Shih et al, 2015).…”
Section: Preferences In Asian Countriesmentioning
confidence: 99%